OPTIMIZATION OF PERIODONSIA CLINICAL LEARNING AT DENTISTRY PROFESSIONAL STUDENTS DURING COVID-19 PANDEMIC - Mutia Rochmawati; Haris Budi Widodo (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
Background: The COVID-19 pandemic has made periodonsia clinical learning in dentistry professional students Jenderal Soedirman University become less optimal because it was implemented online according to government directions. Optimization of periodonsia clinical learning needs to be done so that learning outcomes can still be achieved even in limited conditions due to the COVID-19 pandemic. Objectives : To determine the effectiveness of optimization periodonsia clinical learning which is implemented online. Methods: This reserach is a quasi experimental with a pretest posttest research design. The participants in this research were dentistry professional students which amounted to 18 people. The pretest and posttest scores ​​were analyzed using the Shapiro-Wilk test and Wilcoxon signed ranks. Results: The optimization periodonsia clinical learning program consists of 4 activities which include: (1) Explanation clinical periodonsia learning modules, (2) Explanation SOP for clinical periodonsia procedures, (3) Video presentation of clinical periodonsia procedures, (4) Implementation of case studies regarding the clinical periodonsia procedures. The mean pretest score was 47.72 and the mean posttest score was 98.44. The data showed an increase in the value of 106.28%. Conclusion: The optimization of periodonsia clinical learning program is effective in helping dentistry professional students Jenderal Soedirman University during the online learning process